ANALISIS TEATER SEBAGAI BENTUK SENI YANG MENGGUGAH DAN MENCERMINKAN KEHIDUPAN - Siti Suwadah Rimang; Magfira Aulia; Sudarsono (STKIP Subang, 2026)
Theater in Indonesia has undergone significant development from traditional to contemporary forms, reflecting cultural values, moral teachings, and social critiques within society. This research examines the role of theater in moral education, innovative explorations in contemporary theater, and adaptation to the digital era. A literature review method was employed to analyze various sources on the history, roles, and challenges of theater in Indonesia. Findings indicate that theater serves not only as entertainment but also as a tool for stimulating critical thinking and social empathy. The primary challenge in the digital age is maintaining the essence of theater in a digital format that allows broad access while preserving intimate interaction between artists and audiences.